The Role of Human Capital and Organizational Capital in the Profitability of Agricultural Bank Branches in Greater Tehran - Mir Khodarahmi, Sayeh; Asgari, Mohammad Reza; Saleh Ardestani, Abbas (Future of Work and Digital Management Journal, 2024)
The present study aimed to determine the role of human capital and organizational capital in explaining the profitability of Agricultural Bank branches in Greater Tehran and to examine whether these intellectual capital dimensions contribute to branch financial performance across different branch grades. This study employed a descriptive-correlational survey design. The statistical population consisted of employees and profitability records of Agricultural Bank branches in Greater Tehran. Using stratified random sampling, 141 employees from 39 profitable branches, including premium, Grade 1, Grade 2, and Grade 3 branches, were selected. Data on human capital and organizational capital were collected using a researcher-developed questionnaire whose validity was confirmed through expert evaluation and exploratory factor analysis, while reliability was established through Cronbach’s alpha coefficients. Profitability data were extracted from official financial records of the selected branches. Data analysis was conducted using descriptive statistics, independent-samples t-tests, one-way analysis of variance, Pearson correlation coefficients, and simple and multiple regression analyses. The results indicated that there were no significant differences in human capital or organizational capital based on gender, age, organizational position, or work experience. Significant differences were observed across educational levels for both human capital and organizational capital. Correlation analysis revealed a significant positive relationship between human capital and profitability, whereas organizational capital was not significantly associated with profitability in the overall sample. Regression analyses demonstrated that human capital significantly predicted profitability and represented the strongest explanatory variable. At the branch level, intellectual capital significantly predicted profitability in premium and Grade 1 branches, while no significant predictive relationship was observed in Grade 3 branches. The strongest effects were observed for human capital, suggesting that employee knowledge, skills, and professional competencies constitute critical drivers of branch financial performance. The findings demonstrate that human capital is a key determinant of profitability in Agricultural Bank branches, while organizational capital plays a supportive but less direct role. The results emphasize the strategic importance of investing in employee development, knowledge enhancement, and competency-building initiatives to improve branch profitability and strengthen long-term organizational performance.